2017
DOI: 10.1590/1516-3180.2016.0270210217
|View full text |Cite
|
Sign up to set email alerts
|

Somatic maturation and the relationship between bone mineral variables and types of sports among adolescents: cross-sectional study

Abstract: CONTEXT AND OBJECTIVE: Peak height velocity (PHV) is an important maturational event during adolescence that affects skeleton size. The objective here was to compare bone variables in adolescents who practiced different types of sports, and to identify whether differences in bone variables attributed to sports practice were dependent on somatic maturation status. DESIGN AND SETTING: Cross-sectional study, São Paulo State University (UNESP). METHODS:The study was composed of 93 adolescents (12 to 16.5 years old… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 24 publications
0
2
0
3
Order By: Relevance
“…In this regard, it is possible that the scarce differences observed are to be interpreted in relation to the selection of these athletes. In line with these findings, Agostinete et al [40] showed that the FM% is higher in young sedentary adolescents than in those who practice sports, without any impact from the maturity status. Moreover, previous studies have shown that FM% decreases with growth, showing a peak around 16 years, and then remaining constant [41,42].…”
Section: Discussionmentioning
confidence: 68%
“…In this regard, it is possible that the scarce differences observed are to be interpreted in relation to the selection of these athletes. In line with these findings, Agostinete et al [40] showed that the FM% is higher in young sedentary adolescents than in those who practice sports, without any impact from the maturity status. Moreover, previous studies have shown that FM% decreases with growth, showing a peak around 16 years, and then remaining constant [41,42].…”
Section: Discussionmentioning
confidence: 68%
“…In the general population, %FM decreases with growth, shows a peak around 16 years [33], and then remains constant [34]. Additionally, Agostinete et al [35] showed that the %FM is higher in young sedentary adolescents than in those who practice sports, without any impact of the maturity status.…”
Section: Discussionmentioning
confidence: 99%
“…25 Em decorrência do aumento que ocorre na massa óssea 27,28 e composição corporal 28,29 relativos a idade cronológica e maturacional, 1,27,30 os resultados do presente estudo sugerem que não há influência dos parâmetros BMD, BMC, MG, MM, MO e %G no desempenho da velocidade da partida em jovens futebolistas. Estes resultados podem sugerir a existência de um período de modificação óssea e muscular efetiva, 27 podendo ser melhorado através de eventos maturacionais ocorridos nos anos anteriores e após o PVC, 31 cujos aumentos positivos na densidade óssea (Pré-PVC), 23,24,27,32,33 TMT (durante PVC) 28,33 e TGT (Pós-PVC) 29 , podem não influenciar o desenvolvimento da velocidade dos jovens futebolistas durante as partidas.…”
Section: Discussionunclassified